Glutamate Activity Regulates and Dendritic Development of J-RGCs - Elias, Eerik; Yang, Ning; Wang, Ping; Tian, Ning (Frontiers in Cellular Neuroscience, 2018)
Retinal ganglion cells (RGCs) have a wide variety of dendritic architectures, which are critical for the formation of their function-specific synaptic circuitry. The developmental regulation of the dendrites of RGCs is thought to be subtype dependent. The purpose of this study is to characterize the dendritic development of a genetically identified RGC subtype, JamB RGCs (J-RGCs), and the roles of glutamate receptor activity on the dendritic development of these cells. We show that the dendrites of J-RGCs are strictly ramified in the outer portion of the inner plexiform layer (IPL) of the retina at the age of postnatal day 8 (P8), mimicking the ramification pattern of adults. However, several other important features of dendrites undergo substantial developmental refinement after P8. From P8 to P13, the dendritic development of J-RGCs is characterized by a dramatic increase of dendritic length and the size of the dendritic field. After eye opening, the dendritic development of J-RGCs is characterized by a tremendous decrease of the number of dendritic protrusions (spine-like structures) and a consolidation of the size of the dendritic field. To determine whether the dendritic development of J-RGCs is regulated by glutamatergic activity, we conditionally knocked out the expression of an obligatory subunit of N-methyl-D-aspartate receptors (NMDARs), NR1 (Grin1), in J-RGCs. We found that J-RGCs with the NMDAR mutation have decreased dendrite outgrowth and dendritic field expansion but increased number of dendritic protrusions before eye opening. To determine if visual experience regulates the development of J-RGC dendrites, we raised the mice in complete darkness after birth. Light deprivation prevented the decrease in the number of dendritic protrusions and the consolidation of the dendritic field of wild type (WT) mice after eye opening. However, light deprivation has no additional effect on the number of dendritic protrusions or the size of the dendritic field of J-RGCs with NMDAR mutation. Together, these results revealed the roles of light stimulation and NMDAR activity on the dendritic development of J-RGCs.